Peculiarities of appointing and conducting forensic examinations under martial law (Bulletin of Kharkiv National University of Internal Affairs, 2023)
It has been proved that criminal justice is a procedure regulated by the norms of current criminal procedure legislation for the activities of specially authorized subjects (bodies of inquiry, preliminary investigation, prosecution, etc.) to determine the circumstances relating to the commission of criminal offences, conduct pre-trial investigation, hold court hearings, render decisions and impose punishment for criminal offences. It has been noted that forensic examination is a special study carried out by highly qualified persons, in accordance with the established procedures and methods, with the aim of obtaining objective and reliable information about an object or event which is the subject of a trial. Forensic examination is one of the key means of evidence in criminal proceedings. Its key purpose is to conduct a specialised investigation to obtain objective and reliable data about a particular object, which can be used as evidence in criminal proceedings. Forensic examinations can be conducted in various fields, such as medicine, physics, chemistry, ballistics, graphology and others, and the data collected can be important for the course of criminal proceedings.It has been noted that under martial law, there are fundamentally new features of the appointment and conduct of forensic examinations. At the same time, the need to reduce bureaucratic procedures in the course of appointing examinations, to introduce certain elements of electronic document flow into this process, to reduce the timeframe for conducting certain examinations with their mandatory preliminary differentiation depending on the degree of complexity, and to ensure that such differentiation is legally enshrined in law are also emphasised.
Keywords: expertise; forensic examination; evidence; criminal proceedings; martial law.